Nano-SnCl4.SiO2, an efficient catalyst for synthesis of benzimidazole drivatives as antifungal and cytotoxic agents - Leila Zamani; Zeinab Faghih; Kamiar Zomorodian; Bi Bi Fatemeh Mirjalili; Asghar Jalilian; Soghra Khabnadideh (Wolters Kluwer Medknow Publications, 2019)
The concept of green chemistry has made significant impact on many frontages including the use of green solvents or sustainable catalyst materials. Benzimidazole ring is an important nitrogen-containing heterocyclic, which exhibits a broad spectrum of bioactivities and are widely utilized by the medicinal chemists for drug discovery. A simple and efficient method was developed for the synthesis of some benzimidazole derivatives via reaction of o-phenylenediamine and substituted aldehydes in the presence of nano-SnCl4/SiO2 as a mild catalyst. Ten 2-substituted benzimidazole compounds (J1-J10) were synthesized. All compounds were evaluated against different species of yeasts and filament fungi using broth micro dilution method as recommended by clinical and laboratory standard institute. Among these compounds, the active ones were chosen for their cytotoxic activities evaluation against MCF-7 and A549 cell lines using MTT method. Compound J2 showed the best antifungal activity against all tested species. Compounds J5-J7 had also desirable antifungal activities. Our cytotoxic results were also similar to the antifungal activities except for J7 which had no cytotoxic activity.